KESULITAN MEMPELAJARI KOSAKATA BAHASA JEPANG SISWA KELAS XI SMK PLUS TERPADU PEKANBARU - Simanjuntak, Agustina; Sinaga, Mangatur; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to describe the factors that influence the difficulty of learning Japanese vocabulary and explain the positive and negative responses of students in grade XI high school Plus Terpadu Pekanbaru. This research was conducted at senior high school Plus Terpadu Pekanbaru in class XI students. This research uses descriptive method with quantitative approach, with a poll of all students in grade XI in high school totaling 30 students, sampling is done by purposive sampling which is a technique of determining the sample with special consideration so it is suitable as a sample. Data collection techniques are carried out by distributing questionnaires via google form or via online containing 36 statement items, then the results of the answers to the questionnaire statements were processed using a Likert scale analysis technique to calculate the percentage index of student scores. The based on data analysis, the overall percentage of difficulties in learning Japanese vocabulary is 77 %. This percentage is included in the high category on the percentage criteria score.Key Words: Difficulty, Vocabulary of Japanese